The Role of Contrast-Enhanced Ultrasound in Differentiating Splenic Tuberculosis From Splenic Lymphoma - Zhang, Wenzhi; Yang, Gaoyi; Zhang, Xu; Ni, Tu (Frontiers in Oncology, 2022)
Aim To summarize the features of splenic tuberculosis and splenic lymphoma by contrast-enhanced ultrasound (CEUS) and examine the application of CEUS in differentiating splenic tuberculosis from splenic lymphoma. Methods The ultrasound and CEUS manifestations of 30 cases of splenic tuberculosis and 19 cases of splenic lymphoma were retrospectively analyzed, and the number of lesions, degree of splenomegaly, internal echogenicity, color blood flow signal, and CEUS manifestations of the two diseases were statistically determined. Results A significant difference was noted in the internal echogenicity between splenic tuberculosis and splenic lymphoma lesions, particularly the strip-shaped hyperechoic areas of the lesions. The ultrasound features of perisplenic, retroperitoneal, and superficial lymph node enlargement were found to overlap (p < 0.05). Splenic tuberculosis showed heterogeneous enhancement and non-enhancement, whereas lymphoma showed low enhancement and high enhancement, and CEUS findings were statistically significant in distinguishing both, p < 0.05. Conclusion Splenic tuberculosis is characterized by a lack of blood supply, mostly heterogeneous enhancement, and non-enhancement noted in CEUS. Splenic lymphoma lesions are often characterized by a rich blood supply and homogeneous enhancement on CEUS. CEUS can help identify the microcirculation of lesions in both patients with splenic lymphoma and patients with splenic tuberculosis. Thus, CEUS has great application value.